Scavenging Tumor‐Derived Small Extracellular Vesicles by Functionalized 2D Materials to Inhibit Tumor Regrowth and Metastasis Following Radiotherapy. (14th July 2022) - Tu, Zhaoxu; Zhu, Yuefei; Xiao, Yongqiang; Chen, Jie; Shannon, Sydney; Zhang, Fan; Li, Zhengwei; Zhou, Jie; Hu, Hanze; Ho, Tzu‐Chieh; Gao, Wenlong; Shao, Dan; et al.
Abstract: Radiotherapy is essential for treating unresectable or metastatic breast cancer, but radiotherapy‐induced tumor cell death generates small extracellular vesicles (sEVs) that promote tumor regrowth and metastasis following treatment. Here cationic nanosheets with a high sEVs‐binding capacity that suppress sEVs‐induced tumor regrowth and metastasis following radiotherapy is developed. Molybdenum disulfide (MoS2 ) monolayers are prepared by using lithium ions as intercalation agents, and are functionalized with cationic polyamidoamine (PAMAM) dendrimers. The MoS2 ‐PAMAM particles exhibit a corrugated sheet‐like nanostructure with a larger surface‐to‐volume ratio than spherical PAMAM‐functionalized particles, resulting in greater sEVs binding capacity. Treatment of MDA‐MB‐231 human breast cancer cells with the MoS2 ‐PAMAM nanosheets reduces sEVs‐induced Toll‐like receptor activation and tumor cell proliferation, migration, and invasion to a greater extent than treatment with spherical PAMAM nanoparticles. In a mouse 4T1 metastatic breast cancer model, the nanosheets exhibit greater inhibition of tumor regrowth and metastasis after radiotherapy than the spherical nanoparticles, demonstrating the potential of these sEVs‐scavenging nanosheets for improving outcomes for breast cancer radiotherapy patients. The work reveals a pivotal role of the 2D sheet‐like materials in binding sEVs, indicating the significance of nanoscale geometry in developing the next‐generation sEVs‐scavenging biomaterials. Abstract : Cationic nanosheets with a large surface‐to‐volume ratio are created by functionalizing MoS2 sheets with polyamidoamine (PAMAM) dendrimers. These MoS2 ‐PAMAM nanosheets exhibit a greater small extracellular vesicles (sEVs) binding capacity than PAMAM‐functionalized nanospheres, greater suppression of sEVs‐induced toll‐like receptor activation, tumor cell migration, and proliferation in vitro. They also more effectively inhibit radiotherapy‐induced tumor regrowth and metastasis in vivo.